Negative electrode sheet, secondary battery, battery module, battery pack and power-consuming device
By controlling the nitrogen content in the coating layer of the negative electrode sheet and forming a gradient distribution, the problem that existing graphite negative electrode materials are difficult to meet the needs of fast charging and discharging under high magnification conditions is solved, and the fast charging performance of secondary batteries is improved and lithium ion transmission capacity is enhanced.
Patent Information
- Application Number
- CN202210031892.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-12
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-01-12
AI Technical Summary
The existing graphite anode materials are difficult to meet the fast charging and discharging requirements of lithium-ion secondary batteries under high magnification conditions.
By controlling the content of nitrogen elements in the coating layer of the negative electrode sheet, it is distributed in a gradient direction in the thickness direction, and the nitrogen content of the first coating is higher than that of the second coating, thereby improving the lithium-philicity and lithium of the negative electrode sheet. The rate of ions.
The fast charging performance of the secondary battery is improved, the solvation effect of lithium ions is suppressed, the migration ability of lithium ions is improved, and the kinetic performance of the negative electrode sheet is enhanced.
Smart Images

Figure CN115810707B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to a negative electrode plate, a secondary battery, a battery module, a battery pack and an electrical device. Background Art
[0002] In recent years, as the application scope of lithium-ion secondary batteries has become more and more extensive, lithium-ion batteries are widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As lithium-ion secondary batteries have made great progress, higher requirements have been put forward for their energy density, cycle performance and safety performance.
[0003] As a negative electrode material, graphite has become the first choice for negative electrode active materials of commercial lithium-ion secondary batteries due to its low cost, convenient production, and actual capacity close to theoretical capacity. Usually used as negative electrode materials, including natural graphite and artificial graphite, but as people's requirements for the charging speed of secondary batteries are getting higher and higher, the existing graphite is difficult to meet the requirements of secondary battery rate performance in actual use. Therefore, the existing graphite modification technology still needs to be improved. Summary of the invention
[0004] Technical problem to be solved by the invention
[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide a negative electrode plate, the nitrogen content of which is gradiently distributed in the thickness direction and has good lithium affinity, thereby improving the rate performance of a secondary battery using the negative electrode plate.
[0006] Technical solutions to solve problems
[0007] In order to achieve the above-mentioned objectives, the present application provides a negative electrode plate, a secondary battery, a battery module, a battery pack and an electrical device.
[0008] A first aspect of the present application provides a negative electrode plate, comprising a coating layer and a current collector, wherein the coating layer is located on at least one surface of the current collector, and the coating layer comprises a first coating layer and a second coating layer, wherein the first coating layer is coated on the surface of the current collector, and the second coating layer is coated on the surface of the first coating layer, wherein the first coating layer comprises nitrogen-doped graphite, and the second coating layer comprises at least one of nitrogen-doped graphite and non-nitrogen-doped graphite, and the total nitrogen content of the first coating layer is greater than the total nitrogen content of the second coating layer.
[0009] Therefore, the present application controls the content of nitrogen doped in graphite so that the total nitrogen content in the first coating is higher than the total nitrogen content in the second coating, and the nitrogen content is distributed in a gradient in the thickness direction of the negative electrode plate, so that the negative electrode plate has good lithium affinity, inhibits the solvation effect of lithium ions, improves the transmission rate of lithium ions, and lithium ions can quickly pass through the second coating to reach the first coating, thereby improving the fast charging performance of the secondary battery. The inventor of the present application speculates that this is because the electronegativity of nitrogen is greater than that of carbon, and the graphite doped with nitrogen has more active sites and better binding ability to lithium ions.
[0010] In any embodiment, the weight proportion of nitrogen in the first coating layer is 1-15% relative to the total weight of the first coating layer, and / or the weight proportion of nitrogen in the second coating layer is 0-3% relative to the total weight of the second coating layer.
[0011] Therefore, when the weight ratio of nitrogen elements in the first coating and the second coating is within the above range, the total nitrogen elements in the negative electrode plate are distributed in a gradient, the nitrogen content in the first coating is high, the electronegativity is large, the binding ability to lithium ions is strong, the migration resistance of lithium ions in the negative electrode plate is small, and the lithium ions can quickly pass through the second coating to reach the first coating, thereby improving the kinetic performance of the negative electrode plate and the fast charging performance of the secondary battery.
[0012] In any embodiment, in the graphite contained in the first coating layer and the second coating layer, the weight ratio of nitrogen element to carbon element is (0-15):100, optionally, (0-6):100.
[0013] Therefore, when the weight ratio of nitrogen element to carbon element in the graphite contained in the first coating and the second coating is within the above range, the graphite has more active sites and has a good adsorption capacity for lithium ions, which reduces the influence of lithium ions due to the solvation effect in the electrolyte, improves the transmission capacity of lithium ions at the solid-liquid interface, and thus improves the kinetic performance of the secondary battery.
[0014] In any embodiment, the graphite has a Dv50 of 7-30 μm.
[0015] Therefore, in this application, when the Dv50 of graphite is not within the above range, the following situations can be avoided: if the Dv50 of graphite is too small, there will be too many particle powders, which may be difficult to evenly disperse in the slurry; otherwise, it may cause too many scratches on the coated negative electrode sheet particles. At the same time, if the Dv50 is too large, it may increase the transmission path of lithium ions between graphite particles, thereby causing the lithium ion embedding speed to be too slow. Therefore, from the perspective of ensuring the dynamic performance and processing performance of the negative electrode sheet, the Dv50 of graphite is selected from the above range.
[0016] In any embodiment, the thickness of the first coating is 3-300 μm, optionally 20-200 μm, and / or the thickness of the second coating is 30-180 μm. Therefore, from the perspective of ensuring the convenience of assembling the battery cell, the thickness of the first coating and the second coating is selected from the above range.
[0017] In any embodiment, the cold pressed density of the negative electrode sheet is 0.5-2.5 g / cm 3 , optionally, 1.3-1.9 g / cm 3 Therefore, when the cold pressing density of the negative electrode sheet is within the above range, the graphite particles in the negative electrode sheet can be in close contact with each other, which is beneficial to the transmission of lithium ions, and at the same time, it also has good wettability to the electrolyte.
[0018] A second aspect of the present application provides a secondary battery, comprising the negative electrode sheet of the first aspect of the present application.
[0019] A third aspect of the present application provides a battery module, comprising the secondary battery of the second aspect of the present application.
[0020] A fourth aspect of the present application provides a battery pack comprising the battery module of the third aspect of the present application.
[0021] The fifth aspect of the present application provides an electrical device comprising at least one selected from the secondary battery of the second aspect of the present application, the battery module of the third aspect of the present application, or the battery pack of the fourth aspect of the present application.
[0022] Effects of the Invention
[0023] The present application controls the content of nitrogen doped in graphite so that the total nitrogen content in the first coating is higher than the total nitrogen content in the second coating, and the nitrogen content is distributed in a gradient in the thickness direction of the negative electrode plate, so that the negative electrode plate has good lithium affinity, inhibits the solvation effect of lithium ions, and improves the transmission rate of lithium ions. Lithium ions can quickly pass through the second coating to reach the first coating, thereby improving the fast charging performance of the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of a negative electrode sheet according to one embodiment of the present application.
[0025] Figure 2 is a schematic diagram of a secondary battery according to one embodiment of the present application.
[0026] Figure 3 yes Figure 2 An exploded view of a secondary battery according to an embodiment of the present application is shown.
[0027] Figure 4 is a schematic diagram of a battery module according to an embodiment of the present application.
[0028] Figure 5 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0029] Figure 6 yes Figure 5 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0030] Figure 7 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0031] Description of reference numerals:
[0032] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION
[0033] Below, the embodiments of the negative electrode plate, secondary battery, battery module, battery pack and electrical device of the present application are specifically disclosed with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0034] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0035] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0036] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0037] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0038] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0039] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0040] Negative electrode
[0041] In one embodiment of the present application, the present application proposes a negative electrode plate, including a coating layer and a current collector, the coating layer is located on at least one surface of the current collector, the coating layer includes a first coating layer and a second coating layer, the first coating layer is coated on the surface of the current collector, and the second coating layer is coated on the surface of the first coating layer, wherein the first coating layer contains nitrogen-doped graphite, the second coating layer contains at least one of nitrogen-doped graphite and non-nitrogen-doped graphite, and the total nitrogen content of the first coating layer is greater than the total nitrogen content of the second coating layer.
[0042] Although the mechanism is not clear, the applicant has unexpectedly discovered through a large number of experiments that by controlling the content of nitrogen doped in graphite, the total nitrogen content in the first coating is higher than the total nitrogen content in the second coating, and the nitrogen content is distributed in a gradient in the thickness direction of the negative electrode sheet, so that the negative electrode sheet has good lithium affinity, inhibits the solvation effect of lithium ions, improves the transmission rate of lithium ions, and lithium ions can quickly pass through the second coating to reach the first coating, thereby improving the fast charging performance of the secondary battery. The inventor of this application speculates that this is because the electronegativity of nitrogen is greater than that of carbon, and the graphite doped with nitrogen has more active sites and better binding ability for lithium ions.
[0043] In some embodiments, the weight proportion of nitrogen in the first coating layer is 1-15% relative to the total weight of the first coating layer, and / or the weight proportion of nitrogen in the second coating layer is 0-3% relative to the total weight of the second coating layer.
[0044] Therefore, when the weight ratio of nitrogen elements in the first coating and the second coating is within the above range, the total nitrogen elements in the negative electrode plate are distributed in a gradient, the nitrogen content in the first coating is high, the electronegativity is large, the binding ability to lithium ions is strong, the migration resistance of lithium ions in the negative electrode plate is small, and the lithium ions can quickly pass through the second coating to reach the first coating, thereby improving the kinetic performance of the negative electrode plate and the fast charging performance of the secondary battery.
[0045] In some embodiments, in the graphite included in the first coating layer and the second coating layer, the weight ratio of nitrogen element to carbon element is (0-15):100, optionally, (0-6):100.
[0046] Therefore, when the weight ratio of nitrogen element to carbon element in the graphite contained in the first coating and the second coating is within the above range, the graphite has more active sites and has a good adsorption capacity for lithium ions, which reduces the influence of lithium ions due to the solvation effect in the electrolyte, improves the transmission capacity of lithium ions at the solid-liquid interface, and thus improves the kinetic performance of the secondary battery.
[0047] In some embodiments, the graphite has a Dv50 of 7-30 μm.
[0048] Therefore, in this application, when the Dv50 of graphite is within the above range, the following situations can be avoided: if the Dv50 of graphite is too small, there will be too many particle powders, which may be difficult to evenly disperse in the slurry; otherwise, it may cause too many scratches on the coated negative electrode plate particles. At the same time, if the Dv50 is too large, it may increase the transmission path of lithium ions between graphite particles, thereby causing the lithium insertion speed to be too slow. Therefore, from the perspective of ensuring the dynamic performance and processing performance of the negative electrode plate, the Dv50 of graphite is selected from the above range.
[0049] In some embodiments, the thickness of the first coating is 3-300 μm, optionally 20-200 μm, and / or the thickness of the second coating is 30-180 μm. Therefore, from the perspective of ensuring the convenience of assembling the battery cell, the thickness of the first coating and the second coating is selected from the above range.
[0050] In some embodiments, the cold pressed density of the negative electrode sheet is 0.5-2.5 g / cm 3 , optionally, 1.3-1.9 g / cm 3 Therefore, when the cold pressing density of the negative electrode sheet is within the above range, the graphite particles in the negative electrode sheet can be in close contact with each other, which is beneficial to the transmission of lithium ions, and at the same time, it also has good wettability to the electrolyte.
[0051] It should be noted that the average volume distribution particle size Dv50 refers to the particle size corresponding to when the cumulative volume distribution percentage of graphite reaches 50%. In the present application, the volume average particle size Dv50 of graphite can be measured by laser diffraction particle size analysis. For example, with reference to standard GB / T19077-2016, a laser particle size analyzer (such as Malvern Master Size 3000) is used for measurement.
[0052] In addition, the secondary battery, battery module, battery pack, and electric device of the present application will be described below with reference to the drawings as appropriate.
[0053] In one embodiment of the present application, a secondary battery is provided.
[0054] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0055] [Positive electrode]
[0056] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.
[0057] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0058] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0059] In some embodiments, the positive electrode active material may adopt a positive electrode active material for a battery that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0060] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0061] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0062] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0063] [Negative electrode]
[0064] The negative electrode plate is the negative electrode plate of the first aspect of the present application.
[0065] [Electrolytes]
[0066] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0067] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0068] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0069] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0070] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0071] [Isolation film]
[0072] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0073] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0074] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0075] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0076] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0077] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 2 The secondary battery 5 is a square structure as an example.
[0078] In some embodiments, reference Figure 3, the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0079] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0080] Figure 4 4 is an example of a battery module. Figure 4 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0081] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0082] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0083] Figure 5 and Figure 6 1 is a battery pack 1 as an example. Figure 5 and Figure 6 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0084] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0085] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.
[0086] Figure 7 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0087] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0088] Example
[0089] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0090] Example 1
[0091]
Preparation of nitrogen-doped graphite
[0092] Preparation of the first coating of nitrogen-doped graphite:
[0093] Melamine: artificial graphite is dispersed in ethanol at a mass ratio of 1.2:1 and stirred at room temperature for 5 hours, and then the ethanol is evaporated at 120°C to obtain material A1. The above material A1 is ground into powder, and then placed in a tubular furnace, calcined at 950°C for 0.5 hours under a nitrogen atmosphere, with a heating rate of 5°C / min, and cooled in the furnace to obtain material B1. The above material B1 is fully washed with boiling water, filtered, and vacuum dried at 70°C for 24 hours to obtain graphite-1. The Dv50 of graphite-1 is 10.5μm.
[0094] The artificial graphite in the second coating layer was not doped with nitrogen and was recorded as Graphite-2. The Dv50 of Graphite-2 was 17.5 μm.
[0095]
Preparation of negative electrode sheet
[0096] First coating: Graphite-1, conductive agent Super P, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) were dissolved in deionized water at a weight ratio of 96.4:0.5:1.9:1.2, and mixed evenly to obtain negative electrode slurry-1. Negative electrode slurry-1 was coated at a weight of CW = 80 mg / 1540.25 mm 2 Coated on the copper foil current collector, dried and cold pressed to obtain the first coating. The first coating thickness = 59 μm. Among them, the cold pressing pressure = 80T, the cold pressing density of the negative electrode sheet = 1.6g / cm 3 .
[0097] Second coating: Graphite-2, conductive agent Super P, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) were dissolved in deionized water at a weight ratio of 96.4:0.5:1.9:1.2, and mixed evenly to obtain negative electrode slurry-2. Negative electrode slurry-2 was coated at a weight of CW = 80 mg / 1540.25 mm 2 Apply on the first coating, dry and cold press to obtain the negative electrode. The second coating thickness = 65μm. Among them, the cold pressing pressure = 80T, the cold pressing density of the negative electrode = 1.6g / cm 3 .
[0098] Example 2
[0099] Except that when preparing the nitrogen-doped graphite in the first coating layer, the weight ratio of melamine to artificial graphite is 3.5:1, the remaining steps are the same as those in Example 1.
[0100] Example 3
[0101] Except that when preparing the nitrogen-doped graphite in the first coating layer, the weight ratio of melamine to artificial graphite is 1.8:1, the remaining steps are the same as those in Example 1.
[0102] Example 4
[0103]
Preparation of nitrogen-doped graphite
[0104] First coating nitrogen-doped graphite:
[0105] Melamine: artificial graphite was dispersed in ethanol at a mass ratio of 2.6:1 and stirred at room temperature for 5 hours, and then the ethanol was evaporated at 120°C to obtain material A1. The above material A1 was ground and placed in a tubular furnace, calcined at 950°C for 0.5 hours under a nitrogen atmosphere, with a heating rate of 5°C / min, and cooled in the furnace to obtain material B1. The above material B1 was washed with boiling water, filtered, and vacuum dried at 70°C for 24 hours to obtain graphite-1. The Dv50 of graphite-1 is 10.5μm.
[0106] Second coating nitrogen-doped graphite:
[0107] Melamine: artificial graphite was dispersed in ethanol at a mass ratio of 1.5:1 and stirred at room temperature for 5 hours, and then the ethanol was evaporated at 120°C to obtain material A2. The above material A2 was ground and placed in a tubular furnace, calcined at 950°C for 0.5 hours under a nitrogen atmosphere, with a heating rate of 5°C / min, and cooled in the furnace to obtain material B2. The above material B2 was washed with boiling water, filtered, and vacuum dried at 70°C for 24 hours to obtain graphite-2. The Dv50 of graphite-2 is 17.5μm.
[0108]
Preparation of negative electrode sheet
[0109] First coating: Graphite-1, conductive agent Super P, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) were dissolved in deionized water at a weight ratio of 96.4:0.5:1.9:1.2, and mixed evenly to obtain negative electrode slurry-1. Negative electrode slurry-1 was coated at a weight of CW = 80 mg / 1540.25 mm 2 Apply it on the copper foil current collector, dry it and then cold press it to obtain the first coating. Among them, the cold pressing pressure = 80T, the cold pressing density of the negative electrode sheet = 1.6g / cm 3 . First coating thickness = 59 μm.
[0110] Second coating: Graphite-2, conductive agent Super P, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) were dissolved in deionized water at a weight ratio of 96.4:0.5:1.9:1.2, and mixed evenly to obtain negative electrode slurry-2. Negative electrode slurry-2 was coated at a weight of CW = 80 mg / 1540.25 mm 2 Apply on the first coating, dry and cold press to obtain the negative electrode. Among them, the cold pressing pressure = 80T, the cold pressing density of the negative electrode = 1.6g / cm 3 . Second coating thickness = 65 μm.
[0111] Example 5
[0112] Except that when preparing the nitrogen-doped graphite in the first coating layer, the weight ratio of melamine to artificial graphite is 3.5:1, the remaining steps are the same as those in Example 4.
[0113] Comparative Example 1
[0114] Except that the artificial graphite in the first coating layer and the second coating layer is not nitrogen-doped, the remaining steps are the same as those in Example 4.
[0115] Comparative Example 2
[0116]
Preparation of nitrogen-doped graphite
[0117] First coating nitrogen-doped graphite:
[0118] Melamine:artificial graphite was dispersed in ethanol at a mass ratio of 1.5:1 and stirred at room temperature for 5 hours, and then the ethanol was evaporated at 120°C to obtain material A1. Material A1 was ground into powder, placed in a tubular furnace, calcined at 950°C for 0.5 hours under a nitrogen atmosphere, with a heating rate of 5°C / min, and cooled in the furnace to obtain material B1. Material B1 was washed with boiling water, filtered, and vacuum dried at 70°C for 24 hours to obtain graphite-1. Dv50 of graphite-1 is 10.5μm.
[0119] Second coating nitrogen-doped graphite:
[0120] Melamine:artificial graphite was dispersed in ethanol at a mass ratio of 2.6:1 and stirred at room temperature for 5 hours, and then the ethanol was evaporated at 120°C to obtain material A2. Material A2 was ground and placed in a tubular furnace, calcined at 950°C for 0.5 hours under a nitrogen atmosphere, with a heating rate of 5°C / min, and cooled in the furnace to obtain material B2. Material B2 was washed with boiling water, filtered, and vacuum dried at 70°C for 24 hours to obtain graphite-2. The Dv50 of graphite-2 was 17.5μm.
[0121]
Preparation of negative electrode sheet
[0122] First coating: Graphite-1, conductive agent Super P, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) were dissolved in deionized water at a weight ratio of 96.4:0.5:1.9:1.2, and mixed evenly to obtain negative electrode slurry-1. Negative electrode slurry-1 was coated at a weight of CW = 80 mg / 1540.25 mm 2 Apply it on the copper foil current collector, dry it and then cold press it to obtain the first coating. Among them, the cold pressing pressure = 80T, the cold pressing density of the negative electrode sheet = 1.6g / cm 3 , first coating thickness = 59 μm.
[0123] Second coating: Graphite-2, conductive agent Super P, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) were dissolved in deionized water at a weight ratio of 96.4:0.5:1.9:1.2, and mixed evenly to obtain negative electrode slurry-2. Negative electrode slurry-2 was coated at a weight of CW = 80 mg / 1540.25 mm 2 Apply on the first coating, dry and cold press to obtain the negative electrode. Among them, the cold pressing pressure = 80T, the cold pressing density of the negative electrode = 1.6g / cm 3 , second coating thickness = 65 μm.
[0124] The relevant parameters of the negative electrode sheets of the above-mentioned Examples 1 to 5 and Comparative Examples 1 to 2 are shown in the following Table 1.
[0125] Table 1: Parameter results of Examples 1 to 5 and Comparative Examples 1 to 2
[0126]
[0127] In addition, the negative electrode sheets obtained in the above Examples 1 to 5 and Comparative Examples 1 to 2 were respectively prepared into secondary batteries as shown below, and performance tests were performed. The test results are shown in Table 2 below.
[0128] (1) Preparation of secondary batteries
[0129]
Preparation of positive electrode
[0130] LiNi 0.8 Co 0.1 Mn 0.1 O2, conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in an N-methylpyrrolidone solvent system in a weight ratio of 94:3:3, and then coated on aluminum foil, dried, and cold pressed to obtain a positive electrode sheet.
[0131]
Preparation of diaphragm
[0132] A porous polymer film made of polyethylene (PE) is used as the isolation membrane.
[0133]
Preparation of electrolyte
[0134] In an inert gas atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), organic solvents ethylene carbonate (EC) / ethyl methyl carbonate (EMC) were mixed evenly in a volume ratio of 2.8:7.2, 14.5% LiPF6 lithium salt was added and dissolved in the organic solvent, and stirred evenly to obtain an electrolyte.
[0135] The positive electrode sheet, the separator and the negative electrode sheets in the above embodiments and comparative examples are stacked in order, so that the separator is between the positive and negative electrodes to play a role of isolation, and then wound to obtain a bare cell. The bare cell is placed in an outer package, and the electrolyte is packaged to obtain a secondary battery.
[0136] (2) Cycling performance test of secondary batteries at 25°C
[0137] The assembled secondary battery is charged and discharged for the first time at 25°C, and constant current and constant voltage charging is performed at a charging current of 0.33C until the upper limit voltage is 4.35V. Then, constant current discharge is performed at a discharge current of 0.33C until the final voltage is 2.8V, and the first discharge capacity value Cn is recorded. Subsequently, a continuous charge and discharge cycle of 0.33Cn / 1Cn, 3.3~4.3V is performed, the discharge capacity value during the cycle is recorded, and the cycle capacity retention rate is calculated. The capacity retention rate of the Nth cycle = (discharge capacity of the Nth cycle / discharge capacity of the first cycle) × 100%. When the cycle capacity retention rate drops to 80%, the number of cycles of the battery is recorded.
[0138] (3) Rate performance test of secondary batteries
[0139] The assembled secondary battery was charged and discharged for the first time at 25°C, and constant current and constant voltage charging was performed at a charging current of 1 / 3C until the upper limit voltage was 4.35V. Then, constant current discharge was performed at discharge currents of 1 / 3C, 3C, and 5C until the final voltage was 2.8V, and the discharge capacity value was recorded.
[0140] Table 2: Performance test results of Examples 1 to 5 and Comparative Examples 1 to 2
[0141]
[0142] According to the above results, the nitrogen content of the first coating layer of the negative electrode sheets in Examples 1 to 5 is greater than that of the second coating layer, which inhibits the solvation effect of lithium ions, prevents the solvent and lithium ions from being co-embedded in graphite, generates an unstable solid electrolyte interface film (SEI film), and accelerates the transmission of lithium ions between the solid-liquid interface, thus achieving good results in improving the cycle performance of the negative electrode sheets. In addition, the rate performance of the negative electrode sheets is also improved, so that lithium ions can be embedded in graphite faster.
[0143] In contrast, in Comparative Examples 1 to 2, no effective improvement was achieved in improving the cycle performance and rate performance of the negative electrode sheet.
[0144] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A negative electrode plate, characterized in that: It includes a coating layer and a current collector, wherein the coating layer is located on at least one surface of the current collector, and the coating layer includes a first coating layer and a second coating layer, wherein the first coating layer is coated on the surface of the current collector, and the second coating layer is coated on the surface of the first coating layer, wherein the first coating layer contains nitrogen-doped graphite, and the second coating layer contains at least one of nitrogen-doped graphite and non-nitrogen-doped graphite, and the total nitrogen content of the first coating layer is greater than the total nitrogen content of the second coating layer.
2. The negative electrode sheet according to claim 1, characterized in that: The weight proportion of nitrogen in the first coating layer is 1-15% relative to the total weight of the first coating layer, and / or the weight proportion of nitrogen in the second coating layer is 0-3% relative to the total weight of the second coating layer.
3. The negative electrode sheet according to claim 1 or 2, characterized in that: In the graphite contained in the first coating layer and the second coating layer, the weight ratio of nitrogen element to carbon element is (0-15):
100.
4. The negative electrode sheet according to claim 3, characterized in that: In the graphite contained in the first coating layer and the second coating layer, the weight ratio of nitrogen element to carbon element is (0-6):
100.
5. The negative electrode sheet according to claim 1 or 2, characterized in that: The Dv50 of the graphite is 7-30 μm.
6. The negative electrode sheet according to claim 1 or 2, characterized in that: The thickness of the first coating layer is 3-300 μm, and / or the thickness of the second coating layer is 30-180 μm.
7. The negative electrode sheet according to claim 6, characterized in that: The thickness of the first coating layer is 20-200 μm.
8. The negative electrode sheet according to claim 1 or 2, characterized in that: The cold pressing density of the negative electrode plate is 0.5-2.5 g / cm 3 .
9. The negative electrode sheet according to claim 8, characterized in that: The cold pressed density of the negative electrode plate is 1.3-1.9 g / cm 3 .
10. A secondary battery, characterized in that: The invention comprises the negative electrode sheet according to any one of claims 1 to 9.
11. A battery module, characterized in that: The secondary battery according to claim 10 is included.
12. A battery pack, characterized in that: A battery module comprising the battery module according to claim 11.
13. An electrical device, characterized in that: The battery comprises at least one selected from the secondary battery of claim 10 , the battery module of claim 11 , or the battery pack of claim 12 .
Citation Information
Patent Citations
Flexible electrode plate with coating layer and preparation method of flexible electrode plate
CN107611341A
Lithium-carbon composite negative pole piece, preparation method thereof and lithium secondary battery
CN108598419A